Repetitive Transcranial Magnetic Stimulation Does Not Improve the Sequence Effect in Freezing of Gait. (4th June 2019) - Ma, Jinghong; Gao, Linlin; Mi, Taomian; Sun, Junyan; Chan, Piu; Wu, Tao
Abstract : Introduction . The sequence effect (SE) is a reason contributing to freezing of gait (FOG) in Parkinson's disease (PD) patients. There is no effective treatment for the SE. The objective of the current study is to investigate the effect of repetitive transcranial magnetic stimulation (rTMS) on the SE in PD patients with FOG. Methods . 28 PD patients with FOG received either real or sham 10-Hz rTMS over the supplementary motor area (SMA). The effects of rTMS on the SE, FOG, and some gait parameters were evaluated. Results . rTMS did not improve the SE. Real rTMS had beneficial effects on FOG and some gait parameters, and this effect lasted for at least four weeks. Conclusions . High-frequency rTMS over the SMA cannot alleviate the SE in PD patients with FOG. rTMS has a long-lasting beneficial effect on FOG; however, this effect is not achieved by improving the SE but may be through improving some other gait parameters.